2003
DOI: 10.1074/jbc.m208834200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Mitogen-activated Protein Kinases Erk1/2 by Erythropoietin Receptor via a Gi Protein βγ-Subunit-initiated Pathway

Abstract: We have recently shown that a heterotrimeric G i protein is coupled to the erythropoietin (Epo) receptor. The G i protein constitutively associates in its heterotrimeric form with the intracellular domain of Epo receptor (EpoR). After Epo stimulation G i is released from the receptor and activated. In the present study we have investigated the functional role of the heterotrimeric G i protein bound to EpoR. In Chinese hamster ovary cells expressing EpoR, the G i inhibitor pertussis toxin blocked mitogen-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…7). This is actually similar to previous findings in CHO cells where EPO activation of ERK was G i -dependent (27). EPO also induces phosphorylation of Akt by 1.88 Ϯ 0.42-fold increase over basal (n ϭ 4, p Ͻ 0.05) (Fig.…”
Section: Cardiac Function Following I/r and Epo Treatment-allsupporting
confidence: 81%
See 1 more Smart Citation
“…7). This is actually similar to previous findings in CHO cells where EPO activation of ERK was G i -dependent (27). EPO also induces phosphorylation of Akt by 1.88 Ϯ 0.42-fold increase over basal (n ϭ 4, p Ͻ 0.05) (Fig.…”
Section: Cardiac Function Following I/r and Epo Treatment-allsupporting
confidence: 81%
“…In recent studies performed to define EPO-mediated regulation of the ERK cascade, several different pathways have been identified that can ultimately lead to ERK activation including PI3K, which may use an atypical protein kinase C for EPOinduced ERK activation in CHO-K1 cells (27). All ERK pathways appear to be initiated through effectors binding to phosphorylated tyrosines located in the intracellular domain of the EPO-R (35).…”
Section: Discussionmentioning
confidence: 99%
“…56 In contrast, the presently observed strong activation of ERKs via EpoR-HM in primary erythroblasts suggests that PY sites may be nonessential for ERK activation. Candidate factors that might couple EpoR-HM (and perhaps the wt-EpoR) to ERKs are presently undefined, but G-proteins as well as PKCs stimulate MAPK modules 57,58 and represent 2 sets of potentially Epo-regulated candidate effectors. Based on the substantial in vivo activity exerted by EpoR-HM, such Epo-regulated pathways should be of interest to define.…”
Section: Discussionmentioning
confidence: 99%
“…33,34) The inovolvement of G i in phosphorylation of ERK1/2 was reported in the case of other GPCRs, such as dopamine D 2 receptor 35) and erythropoietin receptor. 36) In the case of TP, however, there are distinct reports about the involvement of G i in the phosphorylation of ERK1/2. Although it was shown that G i participated in TPmediated ERK1/2 phosphorylation in human bladder cancer cells, 37) Miggin and Kinsella 26) reported that G i did not participate in TP-mediated ERK1/2 phosphorylation in human uterine smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%